Existence of the bound form of prolipoprotein in Escherichia coli B cells treated with globomycin. - Inukai, M (1979)
A murein-bound form of prolipoprotein was found in the cell envelope fraction of globomycin-treated Escherichia coli B. We suggest therefore that proteolytic cleavage of prolipoprotein to mature lipoprotein is not essential for the transpeptidation of the lipoprotein to peptidoglycan.